Sports and Technology - Pandey, Ashutosh (Unity Journal, 2021)
This research article examines the use of technology in sports from a double-edged perspective. This article focuses on some of the remarkable technological advancement which has revolutionized and impeded the sport industry as whole. From introduction of modern technology in training of players to reducing the faults in game through various measures like Video Assistant Referee and Goal Line Technology, the development and implementation of technology in sports has played a vital role in improving the standard of game, for players as well as for spectators. However, only a few research works have been conducted and a minimum of articles have been written on the hindrances caused by those technology and problems with proper implementation of technology in sports. This paper is prepared after in-depth research of news by various sports portals, channels and magazines along with the views of experts of diff erent sports who have recognized the need and development of technology in sports. This paper further elucidates on how the advancement has benefi tted and the fi eld of sports with substantial infl uence on game results by mitigation of errors which were inevitable when technology was not used in past. Based on elucidation of different primary and secondary sources, such as journal articles, newspapers, magazines, sports portals and events, case laws, statutes, this research article is mostly qualitative than quantitative.